The Integration of Sharia Electronic Money for the Enhancement of National Economy: A Sharia Economic Law Perspective: Integrasi Uang Elektronik Syariah Untuk Peningkatan Perekonomian Nasional: Perspektif Hukum Ekonomi Syariah - Ahnaf Ra’id Rizqullah; Zazkia Diah Marselinda; Dea Haurjana Sabila Haurjana Sabila; Waluyo Waluyo (Program Studi Hukum Ekonomi Syari'ah, 2025)
This research discusses the strategic contribution of Sharia e-money in supporting the growth of Indonesia's national economy. Sharia e-money, regulated by DSN-MUI Fatwa No. 116 of 2017, combines the convenience of digital transactions with Sharia compliance, providing legal certainty for Muslims. Trough a qualitative approach and literature review, this study examines the role of Sharia e-money in expanding financial inclusion, reducing transaction costs, strengthening the Sharia-based MSME ecosystem, and facilitating digital zakat and waqf. Beyond its economic benefits, sharia e-money also faces challenges such as sharia compliance in transactions, digital security, sustainable business models, and regulatory synchronization. Proposed solutions are based on technology, digital sharia literacy education, and regulatory harmonization. Sharia e-money has the potential to be a driver of inclusive and sustainable economic growth in accordance with Islamic values.